183. Candidaemia in Children and Importance of Central Venous Catheter Removal - Arikan, Kamile (Open Forum Infect Dis, 2019)
BACKGROUND: Candida is the most common cause of invasive fungal infection in healthcare settings and is associated with significant increases in healthcare resource utilization and attributable mortality. METHODS: This study was conducted in a pediatric tertiary care hospital from Turkey. We conducted a retrospective analysis in children ≤18 years with blood culture-proven candidaemia identified between December 2013 and November 2017. Sociodemographic variables,underlying condition, mortality, additional risk factors, origin of specimens were all recorded. RESULTS: A total of 236 episodes of candidaemia were identified over the study period. The median age of the patients was 600 days (4-6482). 106 specimens (44.9%) were cultured from patients under 1 year of age and 15 of 106 specimens were cultured from neonates. The most frequently isolated Candida spp. were C. albicans (42.%), followed by C. parapsilosis (30.5%), C. glabrata (7.6%), C. tropicalis (6.4%), C. krusei (2.5%), C. lusitaine (2.5%), C. dubliniensis (2.1%), C. kefir (0.8%), and C. pelliculosa (0.4%). In 11 of the 236 episodes (4.5%), two Candida spp were cultured at the same time.The most common coinfection was C. albicans and C. parapsilosis. 112 of the 236 episodes (47.5%) was due to central venous catheter-related blood stream infection. 47.5% of these patients were receiving total parenteral nutrition at the time of candidemia. Concomitant coagulase negatif staphylococcus bacteremia was present in 50 of 236 candidemia episodes (21.2%). Of 236 isolates, 74 (31.4%) was cultured from peripheral blood culture only, 95 (40.3%) from central venous catheter only, 67 (28.4%) from both peripheral and central catheter blood culture.Trombocytopenia was noted in 117 episodes (49.6%) and neutropenia in 45 episodes (19.1 Of the 112 central venous catheter-related candidemia, 35 (31.3%) resulted in death within 30 days from the onset of candidaemia (Figure 1). In 49 (45.%) episodes of central venous catheter-related candidemia, catheter was not removed and 40% of these episodes resulted as death.Catheter removal, thrombocytopenia, total parenteral nutrion were found to be associated with increased mortality in children under 1 year of age (P < 0.001). CONCLUSION: Clinicians must be aware of candidemia in children due to high risk of mortality. [Image: see text] DISCLOSURES: All authors: No reported disclosures.